P.Vivax Malaria Causing BOOP: A Rare Complication - Sreehari Deshmukh; V B Singh; Babulal Meena; Vishnu Kumar Saini; Sanjay Beniwal; Ashok Thaned (International Journal of Medical Research and Review, 2015)
India and African countries are said to endemic to malaria. P. Falciparum malaria practically can cause anything as we have read in the articles, but complications with P.vivax are not common. Bronchiolitis obliterans with organizing pneumonia (BOOP) is one of the rare lung diseases. Here we are presenting a case of P.Vivax malaria complicated by BOOP which is a very rare complication.